Officer Resignation and the Space Between Theory and Practice. Issue 3 (July 2019) - Menchaca-Bagnulo, Ashleen
Having read the erudite contributions of Dubik, Feaver, Kohn, Mueller, and Snider, I can only supplement our mutual inquiry through the contribution of an analysis of officer resignation from the perspective of Western political thought, particularly as embodied by strands of the civic republic tradition. I believe this tradition can give us a foundation for talking about officer resignation and a means for drawing strict boundaries around when such dissent is appropriate.